PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP DI RUMAH SAKIT UMUM RAJAWALI CITRA 2022 - Hodiri Adi Putra (Universitas Malikussaleh, 2022)
Patient satisfaction is a guideline that must be implemented, with satisfaction the existence of the hospital can be maintained. The purpose of this study was to determine the effect of service quality on inpatient satisfaction. The method used is quantitative with the technique of distributing questionnaires to a research sample of 32 patients. The analysis used is descriptive analysis of multiple linear regression (path analysis), R2 test, F test and T test. The results show that the overall dimensions of service quality have a significant positive influence on patient satisfaction, which means the better the quality of service starting from physical evidence Tangibles, Reliability, Responsiveness, Assurance, Empathy provided by the hospital will be able to increase patient satisfaction